Pengaruh Lama Fermentasi Kulit Kopi Robusta dan Arabika terhadap Mutu Teh Cascara Serta Uji Keama - Sugito, Sugito; Rosidah, Umi; Wijaya, Agus (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Sugito S, Rosidah U, Wijaya A. 2022. The Effect of fermentation time on quality and safety aspect of robusta and arabica cascara. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 1073-081. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The effect of fermentation time of robusta and arabica coffee skin on cascara tea quality and safety was studied in this research. Robusta and arabica coffee skin were collected from Semendo area in Muara Enim District, South Sumatera Province, whereas cascara tea was then produced later. A non factorial completely randomized design was used and one factor was investigated, namely fermentation time of coffee skin (cascara). There were 8 factor levels, including non-fermented arabica cascara, 2, 4 and 6-hour fermented arabica cascara, non fermented Robusta cascara, 2, 4 and 6-hour fermented Robusta cascara. All experiment was carried out in triplicates. Observed parameters were physical (color), chemical (water content, pH value and total phenol content) as well as safety (metal impurities, including Pb, Cu, Zn, Hg and As content) characteristics. The results showed that fermentation time significantly decreased lightness, hue, water content, pH value and total phenol content of brewed tea, whereas chroma increased significantly. In conclusion, the best treatment factor for Robusta cascara was the one that was fermented for 4 hours with the following characteristics: lightness 40.77%, hue 62.45O, water content 5.12%, pH 4.72, and total phenol content 1.92 mgGAE/g, whereas the best treatment factor for Arabica cascara was the one that was fermented for 4 hours with the following characteristics: lightness 42.77%, hue 63.45O, water content 5.42%, pH 4.12, and total phenol content 2.04 mgGAE/g. Furthermore, brewed tea both in Robusta and Arabica contained lower metal impurities compared to SNI standard